C02 quantification using seismic attributes in laboratory experiments - Keshavarz Faraj Khah, Nasser (Curtin University, 2007)
Sequestration has been suggested as a solution for resolving the problem of increasing greenhouse gas emissions. CO2 is the major greenhouse gas which results from using fossil fuels for domestic and industrial purposes. Different geological targets have been suggested as reservoirs for CO2 sequestration with saline aquifers being the focus of this research. Monitoring and verification of injected CO2 into the ground is an essential part of CO2 sequestration because there is a strong requirement to understand and correctly manage the CO2 flow and movement within the reservoir over time. This includes a need to understand mobile CO2 in its all phases (gas, liquid, supercritical and dissolved in formation water). It is now well recognised that monitoring injected liquids in the sub-surface can be done remotely using surface seismic monitoring techniques. Seismic waves are sensitive to the contrast in the physical properties of formation water and CO2. As a gas, the migration path of CO2 has been shown to be easily imaged but such images provide only a qualitative rather than a quantitative solution, which is inadequate to remotely verify storage volumetrics. The complexity of saline aquifer reservoirs containing the different phases of CO2 (a function of reservoir pressure, temperature, and chemical composition and the state of phase of injected CO2) requires a good knowledge base of how the seismic response changes to such changes in CO2 phase and reservoir heterogeneities for verification purposes.In this research, transmission ultrasonic seismic experiments were performed under controlled pressure, temperature and CO2 dissolution conditions in water. Different forms of simulated rock matrix were used to understand how seismic attributes changed with changing sequestration conditions. Data analysis showed that the commonly used approach of seismic velocity analysis is not particularly sensitive to dissolved CO2 whereas seismic amplitude was very sensitive to dissolved CO2 content and is the seismic attribute of choice for the future quantification of CO2. The density increase in formation water brine as a result of CO2 mixture was found to be directly related to transmission amplitude and provides the potential for prediction and thus, remote quantification. Also, there was confirmation during the transmission experiments that seismic amplitude changes markedly when CO2 changes phase from its dissolved form into a gas, as a result of significant attenuation by CO2 bubbles. Analysis showed that the dominant and centre frequency of the spectra also responded to CO2 phase when it changed from dissolved to its free gas form. However, these attributes appear to be of use in a qualitative manner rather than quantitative. The CO2 pre-bubble phase was studied in an attempt to obtain a basic knowledge of the effect on seismic amplitude variation for quantifying dissolved gas amounts with some success. This knowledge has an application in Gas-to-Oil-Ratio mapping in depleting oil fields and can assist the future management of production from fields which are at the stage of near-bubble point due to pressure depletion.The results of this research have an application in time-lapse seismic monitoring and operational management of greenhouse gas sequestration operations. In particular, the VSP and cross-well seismic methods are immediate beneficiaries of this research, with further work required for application to 3-D reflectivity methods in time-lapse surface seismic monitoring.